Evaluation of antenatal care competency with Objective Structure Examination Blended Learning (OSCE-BL) - Ari Indra Susanti; Ariyati Mandiri (Inovasi Kurikulum)
Midwifery students must possess clinical competency before entering clinical practice in the practice area. Assessing clinical competency using Objective Structure Clinical Evaluation (OSCE) is necessary. However, OSCE examiners are limited, so blended learning is carried out. The research aims to determine the learning outcomes of midwifery students using OSCE Blended Learning (BL) in the pregnancy care module. This research used a descriptive cross-sectional method using OSCE scores from 2020 to 2022. That research sample was 92 people using a total sampling technique. Competencies tested in the OSCE are anamnesis, physical examination in the second and third trimester, laboratory examination, and counseling. Processing and analyzing univariate data descriptively. The anamnesis competency score was the greatest mean in 2021 (91.45), physical examination in the second trimester (88.79), and third trimester (88.03). Meanwhile, supporting examinations in 2020 (88.36) and counseling (88.31). In the OSCE evaluation in 2021, only a small number of students did not pass the anamnesis (2 people), physical examination second trimester (2 people), and third trimester (2 people), support (2 people), and counseling (1 person). Method OSCE BL can be used to evaluate pregnancy care competency before midwifery students do clinical practice in the practice area.